PENELITIAN TENTANG KEMAMPUAN SISWA KELAS DUA SMPN 13 PEKANBARU DALAM MENULIS TEKS RECOUNT - Nasution, Ratu Fatimah; Jismulatif, Jismulatif; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to find out the ability of the second year students of SMPN 13 Pekanbaruin writing recount text. The population of the study were all second year students of 2019/2020 as big as 300 persons. Due to the big size of the homogeneus population, the simple random sampling isused to take the sample as manyas 30 students (10%). Writing test was administered to collect the needed data in the form essay of recount text. From the data analysis, it was found that the ability of second year students ofSMPN13 Pekanbaruwas in good level.The highest score is inoriginality. The lowestoneis in grammar. Therefore, the students are expected to study and practice more how to write a recount text based on the generic structure and seven writing aspects applied in curriculum 2013 especially in grammar.KeyWords: Writing, Ability, Recount Text